Pregnancy Outcomes in Uncorrected Ventricular Septal Defect in Tertiary Care Hospital - Halim, Tanzila; Kulsum, Umme; Islam, Md Saiful; Shameem, Md Kibriya; Pasha, Mostofa Midhat; Bari, Ahmed Saiful; Qumruzzaman, Khondoker (University Heart Journal, 2025)
Background: Pregnancy in women with uncorrected ventricular septal defect (VSD) poses significant maternal and fetal risks, yet data from low-resource settings remain limited. Aim of the study: To evaluate maternal, obstetric, and neonatal outcomes in pregnancies complicated by uncorrected VSD at a tertiary care hospital. Methods: A retrospective observational study was conducted at Bangladesh Medical University, Dhaka, Bangladesh over a period of July 2022 to June 2024 on 50 pregnant women with echocardiographically confirmed uncorrected VSD. Maternal cardiac status, obstetric complications, and neonatal outcomes were extracted from medical records. VSDs were classified by size and type. Quantitative data were analyzed using SPSS v26, with continuous variables expressed as mean ± SD and categorical variables as frequencies and percentages. Independent t-tests and Chi-square or Fisher’s exact tests were used for comparisons, with p<0.05 considered significant. Result: Small VSDs predominated (56%), with perimembranous defects most common (74%). Cardiac complications occurred in 7% of small versus 32% of moderate/large VSDs (p<0.01). Preterm delivery (14% vs. 32%, p=0.04) and low birth weight (18% vs. 45%, p=0.02) were higher in moderate/large defects. Cesarean delivery was more frequent in larger defects (55% vs. 36%). Overall, maternal and neonatal outcomes were favorable in small VSDs. Conclusion: Pregnancy in women with uncorrected VSD is generally well tolerated in small defects but carries substantial maternal and fetal risks in moderate to large VSDs. Individualized risk assessment and multidisciplinary care are essential. University Heart Journal 2025; 21(2): 69-74